Peculiarities of Training 13-14-Year-Old Handball Players - Abduyeva, Sitorabonu Savriddin Qizi (Athena: Physical Education and Sports Journal, 2023)
The State Physical Education Institute of Uzbekistan, which provides its services to the training of qualified specialists in the field of physical education and sports, as well as gaining its rightful place in the economic and social sphere of our Republic as a base higher education institution. The issue of studying, analyzing and reporting the relevant conclusions on the sociopedagogical features of the training of qualified specialists in the educational institution is also considered urgent. The results of the study show that mastering the technique of a movement or a set of movements requires sufficient development of physical qualities.